2011
DOI: 10.1371/journal.pone.0027628
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proliferation Rhythm of Neural Progenitor and Oligodendrocyte Precursor Cells in the Young Adult Hippocampus

Abstract: Oligodendrocyte precursor cells (OPCs) are a unique type of glial cells that function as oligodendrocyte progenitors while constantly proliferating in the normal condition from rodents to humans. However, the functional roles they play in the adult brain are largely unknown. In this study, we focus on the manner of OPC proliferation in the hippocampus of the young adult mice. Here we report that there are oscillatory dynamics in OPC proliferation that differ from neurogenesis in the subgranular zone (SGZ); the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…Previous reports have shown that the day-night cycle affects cell cycle progression in a variety of unicellular and multicellular organisms and produces 24-h mitotic rhythms in many tissues, including rapidly dividing epithelia and the hematopoietic system (8,10) and the more slowly renewing mammalian brain (9,11,12,15). However, in these studies, a possible temporal coordination of stem cell divisions remained largely unexplored, because typically, all mitotic cells, not specifically stem cells, were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that the day-night cycle affects cell cycle progression in a variety of unicellular and multicellular organisms and produces 24-h mitotic rhythms in many tissues, including rapidly dividing epithelia and the hematopoietic system (8,10) and the more slowly renewing mammalian brain (9,11,12,15). However, in these studies, a possible temporal coordination of stem cell divisions remained largely unexplored, because typically, all mitotic cells, not specifically stem cells, were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral factors and environmental influences are also known to affect the frequency of cell divisions, adjusting tissue homeostasis to the changing conditions inside and outside the organism (7). Twentyfour-hour rhythms of division have been documented in several mammalian tissues, reflecting dynamic activity in complex populations of dividing cells consisting of stem cells and their differentiating progeny (8)(9)(10)(11)(12)(13)(14)(15). Altered behavioral states, such as insufficient sleep, pregnancy, and physical exercise, induce mitotic activity in the brain and other stem cell-supported tissues (4, 7).…”
mentioning
confidence: 99%
“…27 In cyclin D2-knockout mice, the brain size is smaller and adult neurogenesis is dramatically impaired. [28][29][30][31] Cyclin D2 is essential for expansion of the NSPCs in both embryonic and adult brains, but what is the significance of the biased localization of cyclin D2 in the basal endfoot of the APs? Figure 1.…”
Section: Cyclin D2 and Brain Evolutionmentioning
confidence: 99%
“…cells are also found distributed throughout non-neurogenic areas of the hippocampus. 34 Thus, although we counted cells only within the hilar region of the dentate gyrus, it is similarly unclear as to whether the generation of oligodendrocytes in the Usp9x-deficient hippocampus was a result of NSCs in the SGZ abnormally differentiating toward the oligodendrocytic lineage instead of a neurogenic path, or whether the lack of Usp9x influenced the proliferation of these randomly distributed oligodendrocyte precursors throughout the hippocampus. Again, the use of an inducible NSC-specific Cre driver in future studies will clarify this question.…”
Section: E1235524-4mentioning
confidence: 99%